Metode Dan Gaya Mengajar Yang Relevan Dengan Pendidikan Agama Islam - Yazidul Bushtomi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The various teaching methods relevant to Islamic religious education are as follows: 1. Lecture method, 2. Discussion method, 3. Recitation method, 4. Experimental method, 5. Demonstration method, 6. Field trip method, 7. Method question and answer, 8. Discovery method, 9. Card sort method, 10. Information research method. Teaching style is an activity of the teacher in contact with the process of teaching and learning interaction aimed at overcoming student boredom, so that in teaching and learning situations students always show perseverance, enthusiasm and full participation. The learning method is more procedural in nature, which contains certain stages, while the teaching style is the method used, which is implementative. In other words, the method each chose was the same, but they could have used different techniques. Various teaching styles that are relevant to Islamic religious education are as follows: 1. Classical teaching style, 2. Technological teaching style, 3. Personalized teaching style, 4. Interactional teaching style.